Life in Kings : reshaping the royal story in the Hebrew Bible - Auld, A. Graeme (Atlanta Society of Biblical Literature (SBL) Press, 2017)
"Building on a lifetime of research and writing, A. Graeme Auld examines passages in Samuel, Kings, Chronicles, and Isaiah that recount the same stories or contain similar vocabulary. He advances his argument that Samuel and Kings were organic developments from a deftly crafted, prophetically interpreted, shared narrative he calls the Book of Two Houses--a work focused on the house of David and the house of Yahweh in Jerusalem. At the end of the study he reconstructs the synoptic material within Kings in Hebrew with an English translation"--
The story so far -- Life -- More words -- God-King communication in Jerusalem -- Cultic matters : the synoptic tradition -- Toward the synoptic narrative -- Samuel revisited -- Prophets and kings in Israel -- Rewriting Judah's kings -- Isaiah and Hezekiah -- Reading written Kings -- Shared text sampled
Includes bibliographical references (pages 279-288) and indexes
Text in English with some Hebrew
Keywords: Bible. -- Criticism, interpretation, etc; Criticism, interpretation, etc